Mobile car alarm via bluetooth application - Norsyafiqah, Jamaluddin (2015)
Car alarm has become an essential feature for all car users as it ensure safety to the car and prevent it from being stolen. The purpose of this project is to develop a mobile central-locking and alarm system for car that can be access using android smartphone as the remote control. The system will control all alarm functions in a car such as locking the door, unlocking the door, activate and deactivate the alarm. The Bluetooth technology is used as the control medium between the car and the smartphone. There are few issues being raised that lead to this project development. The first issue is the current car alarm system is not interactive enough and car owner needs an additional alarm remote control plus the car key to bring anywhere. Other issues are the loss of car key, where user can use this application installed in their smartphone as an alternative key to unlock their car. This project is expected to enhance the capability of the existing car alarm system to be more interactive and user friendly.